2018
DOI: 10.1186/s12903-018-0656-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen-planus-associated fibroblasts acquire myofibroblast characteristics and secrete pro-inflammatory cytokines in response to Porphyromonas gingivalis lipopolysaccharide stimulation

Abstract: BackgroundOral lichen planus (OLP) is a chronic inflammatory oral mucosal disease in which comprehensive inflammation-related cytokines are involved. These cytokines are commonly produced by immune cells and specific nonimmune cells including keratinocytes, endothelial cells and fibroblasts. This raises the question of whether fibroblasts in OLP lesions contribute to the inflammatory process upon inflammatory simulation.MethodsPrimary cultured Oral lichen-planus-associated fibroblasts (OLP AFs, n = 5) and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…A number of studies have demonstrated that LPS-induced overproduction of IL-1β, il-6 and TnF-α contributes to the majority of inflammatory responses that are involved in the pathogenesis of inflammatory-stimulated oral bone diseases, including periodontitis (35), peri-implantitis (36) and apical periodontitis (37). By contrast, our previous studies identified that NAC inhibited LPS-mediated synthesis of IL-1β, il-6 and TnF-α (10,26). Thus the present study focused on the secretion of IL-1β, il-6 and TnF-α.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…A number of studies have demonstrated that LPS-induced overproduction of IL-1β, il-6 and TnF-α contributes to the majority of inflammatory responses that are involved in the pathogenesis of inflammatory-stimulated oral bone diseases, including periodontitis (35), peri-implantitis (36) and apical periodontitis (37). By contrast, our previous studies identified that NAC inhibited LPS-mediated synthesis of IL-1β, il-6 and TnF-α (10,26). Thus the present study focused on the secretion of IL-1β, il-6 and TnF-α.…”
Section: Discussionmentioning
confidence: 63%
“…The principal etiological factor for these inflammatory diseases is plaque accumulation ( 7 , 8 ). Among the vast array of oral bacteria, Porphyromonas gingivalis serves a particularly important role in both periodontitis and peri-implant diseases, resulting from the expression of various virulence factors, the most recognizable of which is lipopolysaccharide (LPS) ( 9 , 10 ). LPS, also known as endotoxin, induces a variety of cell types, such as osteoblasts ( 11 ), human umbilical vein endothelial cells ( 12 ) and gingival fibroblasts ( 13 ), to overexpress related inflammatory factors, including interleukin (IL)-1β, IL-6 and tumor necrosis factor α (TNF-α).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portal myofibroblasts promote vascular remodeling underlying cirrhosis formation by releasing microparticles (10). A previous study suggested that OLP-associated fibroblasts acquired the characteristics of myofibroblasts (termed OLP/MFs) (11). Immunophenotypically, myofibroblasts are characterized by the expression of abundant pericellular matrix proteins, including vimentin, α-smooth muscle actin (α-SMA) and fibroblast activation protein (FAP) (11).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 , Ertugrul and colleagues observed that OLP patients were more likely to suffer from infections by Aggregatibacter actinomycetemcomitans , Porphyromonas gingivalis , Prevotella intermedia , Tannerella forsythia , and Treponema denticola , as compared to people not affected by the disease; the conclusion was that all these bacterial species can be involved in periodontal diseases. More recently, Wang et al ( 2018 ) reported that P. gingivalis lipopolysaccharide (LPS) somehow affected fibroblasts in OLP patients, and the cells acquired myofibroblastic characteristics, thus secreting pro-inflammatory cytokines.…”
Section: Bacteria Associated With Oral Lichen Planusmentioning
confidence: 99%